Microeconomics - Pindyck, Robert S.; Rubinfeld, Daniel L. (Upper Saddle River, N.J.; London : Prentice Hall, 2001)
This title emphasises relevance and application to both managerial and public-policy decision making are focused goals of the book. It shows how microeconomics can be used as a tool for decision making.
"International edition"--cover.
Includes bibliographical references and index.
oif 23/04/15
Loan
Keywords: Microeconomics